System Framework Tools For Future CNC Machining - Salleh, Mohd Shukor; Minhat, Mohamad; Che Zainal Abidin, Nik Mohd Farid; Arep @ Ariff, Hambali (2011)
The STEP-NC controller is module-based, consisting of Data Input, Interpreter (STEP/FB Translator), Tool-Path Generator (TPG) and Motion Control module. A STEP-NC data file is used as the input, and a generated part program is used by a machine tool to carry out the task. The research involved working with a generic and native program, thus enabling the controller to have the desired interoperability. STEP/STEP-NC standards (ISO 10303/ISO 14649) and function blocks standard (IEC 61499) include in the system framework, provide the required technologies and tools for the development of a STEP-NC controller. There are five key characteristics of the STEP-NC controller that are Encapsulation, Portability, Interoperability, Configurability and Adaptability. The multi-layered architecture enables modelling and simulation to be tightly integrated with the design process. STEP-NC controller can either perform a simulation as a formal verification, or the function block-based STEP-NC controller can be used as a virtual machining tool and assist users to create the part program using the standard function blocks in the desired order.